A study of prospective analysis of unipolar versus bipolar hemiarthroplasty of hip joint in patients with fracture neck of femur - X., Raja; Sarvesh, Arjun; M., Karthikeyen; Manoharan, A. E. (International Journal of Research in Orthopaedics, 2021)
Background: Femoral neck fractures occur most commonly in elderly females and are a major cause of morbidity and mortality in this age group and require immediate and appropriate management. Aim of the study was to compare the functional outcome of unipolar Austin Moore’s prosthesis (AMP) hemiarthroplasty (HA) and bipolar (BHA) HA with femoral neck fractures using Harris hip score system. Methods: The study was conducted on 60 patients aged above 50 years with fractured neck of femur admitted in Vinayaka missions Kirupananda Variyar medical college and hospital from August 2017 to August 2019. Patients with femoral neck fracture were allocated randomly to have 30 cases of AMP. Results: Out of the 60 cases, the patients in the bipolar (nonmodular) HA group II showed better functional outcomes compared to unipolar (AMP) HA group I after six months follow-ups. At 12 months of follow-up, there was no significant difference between group I (AMP) and group II (BHA). Conclusions: Our study demonstrates, hemiarthroplasty of the hip for femoral neck fractures is a good option in elderly patients. The mortality and morbidity are not high, the operative procedure is simple, complications are less disabling, early weight-bearing and functional results are satisfactory and second surgery are less frequently required.